Gap Analysis Matrix dan Roadmap Smart Transportation Bandar Lampung Berbasis Rujukan Jakarta dan Bogor - Marshanda Anabella; Vanesya Claresta; Muhammad Iyad Irviansyah; Master Edison Siregar (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
The rapid population growth and urbanization in Bandar Lampung have generated substantial pressure on the city’s transportation system, which remains dominated by private vehicles and traditional public transport services. This condition contributes to increasing congestion, travel inefficiency, pollution, and a decline in service quality. This study aims to assess the readiness of Bandar Lampung to implement smart transportation using the seven layers of the Smart City Ecosystem Framework. The research employed a qualitative approach through literature analysis and the application of a Gap Analysis Matrix, with Jakarta and Bogor serving as benchmarks to define the desired state of smart transportation development. The findings indicate that Bandar Lampung is positioned in the emerging category, with the most significant gaps identified in the technology infrastructure, data and information, service integration, and digital innovation layers. The city lacks adequate IoT infrastructure, multimodal integration, and a unified mobility data system. Based on these findings, a 2025–2030 smart transportation roadmap is proposed, focusing on regulatory development, service digitalization, IoT enhancement, multimodal and digital payment integration, fleet modernization, and multi-stakeholder collaboration. This study is expected to support strategic decision-making for promoting a more efficient, integrated, and sustainable urban mobility system in Bandar Lampung.